The Emotional Self : a Sociocultural Exploration. - Lupton, Deborah (SAGE Publications, 1998)
"This addition to a growing number of texts which approach emotions and emotionality from a social constructionist perspective is well written, scholarly, accessible and interesting ... There is both breadth and depth to this work."--Feminism and Psychology This broad-ranging and accessible book brings together social and cultural theory with original empirical research into the nature of the emotional self in contemporary western societies. The emphasis of the analysis is on the emotional self as a dynamic project that is continually shaped and resha.